Case Report: Bullous Pemphigoid Associated With Morphea and Lichen Sclerosus: Coincidental Diseases or Pathogenetic Association? - Maglie, Roberto; Baffa, Maria Efenesia; Montefusco, Francesca; Pipitò, Carlo; Senatore, Stefano; Capassoni, Marco; Maio, Vincenza; Cerinic, Marco Matucci; Antiga, Emiliano; Guiducci, Serena (Frontiers in Immunology, 2022)
Bullous pemphigoid (BP) represents the most common autoimmune bullous disease and is characterized by IgG autoantibodies targeting collagen XVII (BP180). BP has reportedly been occurred in association with other inflammatory skin diseases. Here, we describe the unusual occurrence of BP in a female patient with a concomitant history of generalized morphea (localized scleroderma, LoS) and cutaneous and genital lichen sclerosus (LiS). The occurrence of BP was associated with elevated serum levels of anti-BP180 IgG autoantibodies, which decreased upon clinical remission. Autoimmune bullous diseases and sclerosing dermatitis are immunologically distinct entities, whose association has been rarely described. In this study, we provide a literature review on cases of BP developed in patients with either LoS or LiS. Further, we discussed immunological mechanisms which may have favoured the emergence of BP in our patient.